Comparing Cancer Primary and Secondary Prevention Documentation Between Different Digital Health Approaches in the Emergency Department - Sally K. Stauder; Shalmali R. Borkar; Anna Najor; Adrienne Hunter; Christopher DeStephano; Michael Mohseni (Women's Health Reports)
Background: Decreasing primary care access and increasing emergency department (ED) usage is a potential contributor to declining cancer screening prevalences in those facing barriers to health care access. The ED is a non-traditional yet potentially high-yield setting for implementation of interventions to monitor and increase cancer screening. Methods: An ED-administered survey in July 2022 gathered data on breast, cervical, and colorectal cancer screening, as well as human papillomavirus (HPV) vaccination status of females presenting to the ED for care. This was compared with electronic health record (EHR) data extraction of all ED patients during the same timeframe. Primary outcome was proportion of cancer screening and HPV vaccination not up to date in each group. Results: ED survey was administered to 101 individuals; EHR data was extracted on 2934 patients. Survey versus EHR, respectively, found cervical cancer screening was not up to date in 6.2% vs. 77.6%, breast cancer screening in 14.3% vs. 73.4%, colorectal cancer screening in 22.9% vs. 56.5%, and HPV vaccination in 33.3% vs. 57.8%. p value was < 0.001 for all screening category comparisons between survey and EHR. Discussion: Our data indicate significant discrepancies between self-reported screening history and EHR data. ED survey results were more in line with the observed screening rates in various surveillance systems and published in the literature. This suggests that point-of-care ED survey administration may be more effective in identifying those needing preventative cancer screening, especially in individuals with less access to routine health care.